Pengaruh Profitabilitas, Likuiditas, Leverage, Dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan - Shela Nurhaliza; Desy Mariani (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to analyze the effect of profitability, liquidity, leverage, and company growth on company value in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. The research data was obtained from financial reports and annual reports published officially and publicly by the companies. The research population consists of food and beverage companies listed on the IDX. Using purposive sampling, 56 companies that met the criteria were selected, resulting in 280 observations collected over five years of observation. The data analysis technique used multiple linear regression with the help of the Statistical Package for the Social Science (SPSS) version 22 program. This method was used to test the effect of independent variables consisting of profitability, liquidity, leverage, and company growth on the dependent variable in the form of company value measured by Price to Book Value (PBV) as a market indicator. The results showed that profitability, leverage, and company growth did not affect company value. This indicates that profit performance, funding structure, and asset growth are not dominant factors influencing investor decisions in assessing companies in the food and beverage sub-sector. Conversely, liquidity proved to have a positive and significant effect on company value. This condition shows that the higher a company's ability to meet its short-term obligations, the greater the level of investor confidence that drives a consistent increase in company value. Based on the results of the study, it can be concluded that liquidity is an important aspect that must be considered in efforts to maintain stability, increase company value, and attract investor attention, while profitability, leverage, and company growth were not proven to have a significant effect on the food and beverage sub-sector during the research period.